2021
DOI: 10.3389/fimmu.2020.614960
|View full text |Cite
|
Sign up to set email alerts
|

Dim Light at Night Impairs Daily Variation of Circulating Immune Cells and Renal Immune Homeostasis

Abstract: Dim light at night (dLAN) has become a pervasive part of the modern world, and growing evidence shows its association with increased health risks. Though this link is attributed to a disturbed circadian clock, the underlying mechanisms that can explain how circadian disruption from dLAN causes negative health effects remain unclear. Here, we exposed rats to a light–dark cycle (12:12 h) with low-intensity light at night (~2 lx) for 2 and 5 weeks and explored the steady-state pattern of circulating immune cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
4
23
0
Order By: Relevance
“…In the current study, corticosterone levels remained rhythmic under the ALAN regime but oscillated with lower amplitude and were phase-advanced compared to controls. This changed pattern corresponds with our previous findings, which showed increased daytime corticosterone levels in rats due to ALAN exposure [42]. Glucocorticoids represent an important circadian signal that can set the phase of peripheral oscillators [43].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, corticosterone levels remained rhythmic under the ALAN regime but oscillated with lower amplitude and were phase-advanced compared to controls. This changed pattern corresponds with our previous findings, which showed increased daytime corticosterone levels in rats due to ALAN exposure [42]. Glucocorticoids represent an important circadian signal that can set the phase of peripheral oscillators [43].…”
Section: Discussionsupporting
confidence: 91%
“…Peripherally, ALAN elevates hepatic MAC1 and TNF [ 34 ]. In contrast, one study observed reduced kidney Ccl2 expression following 2 weeks of ALAN [ 80 ].…”
Section: Alan and Inflammationmentioning
confidence: 99%
“…• What is the main finding and its importance? GmbH, Munich, Germany;Okuliarova et al, 2021). Rats were weighed at the end of ALAN week 2 and 5.…”
Section: New Findingsmentioning
confidence: 99%